Binge-like Alcohol Exposure in Adolescence: Behavioural, Neuroendocrine and Molecular Evidence of Abnormal Neuroplasticity… and Return - Brancato, Anna; Castelli, Valentina; Lavanco, Gianluca; Tringali, Giuseppe; Micale, Vincenzo; Kuchar, Martin; D'Amico, Cesare; Pizzolanti, Giuseppe; Feo, Salvatore; Cannizzaro, Carla (Biomedicines, 2021)
Binge alcohol consumption among adolescents affects the developing neural networks underpinning reward and stress processing in the nucleus accumbens (NAc). This study explores in rats the long-lasting effects of early intermittent exposure to intoxicating alcohol levels at adolescence, on: (1) the response to natural positive stimuli and inescapable stress; (2) stress-axis functionality; and (3) dopaminergic and glutamatergic neuroadaptation in the NAc. We also assess the potential effects of the non-intoxicating phytocannabinoid cannabidiol, to counteract (or reverse) the development of detrimental consequences of binge-like alcohol exposure. Our results show that adolescent binge-like alcohol exposure alters the sensitivity to positive stimuli, exerts social and novelty-triggered anxiety-like behaviour, and passive stress-coping during early and prolonged withdrawal. In addition, serum corticosterone and hypothalamic and NAc corticotropin-releasing hormone levels progressively increase during withdrawal. Besides, NAc tyrosine hydroxylase levels increase at late withdrawal, while the expression of dopamine transporter, D1 and D2 receptors is dynamically altered during binge and withdrawal. Furthermore, the expression of markers of excitatory postsynaptic signaling-PSD95; Homer-1 and -2 and the activity-regulated spine-morphing proteins Arc, LIM Kinase 1 and FOXP1-increase at late withdrawal. Notably, subchronic cannabidiol, during withdrawal, attenuates social- and novelty-induced aversion and passive stress-coping and rectifies the hyper-responsive stress axis and NAc dopamine and glutamate-related neuroplasticity. Overall, the exposure to binge-like alcohol levels in adolescent rats makes the NAc, during withdrawal, a locus minoris resistentiae as a result of perturbations in neuroplasticity and in stress-axis homeostasis. Cannabidiol holds a promising potential for increasing behavioural, neuroendocrine and molecular resilience against binge-like alcohol harmful effects.
Keywords: adolescence; binge alcohol drinking; nucleus accumbens; cannabidiol